Self-Heating Mould for Composite Manufacturing - Kondratiev, Andrii; Píštěk, Václav; Purhina, Svitlana; Shevtsova, Maryna; Fomina, Anna; Kučera, Pavel (MDPI, 2021)
The shipbuilding industry, engine manufacturing, aviation, rocket and space technology are promising fields of application for polymeric composite materials. Shape-generating moulding tools with internal heating are used for the creation of a more economically viable method of moulding of internally heated composite structures. The use of a fine-fibered resistive structure in the heated tools allows implementation of effective heating of the composite and elimination of the need for expensive and energy-intensive heating equipment. The aim of this paper was the reduction of energy consumption for internally heated moulding tools by choosing the optimal parameters for their resistive layer. A method for determination of the parameters of the moulding tool resistive layer was developed. This method allows calculation of the heating layer parameters and implementation of the specified time–temperature regime for moulding of the composite structure. It was shown that energy saving for the heated fiberglass shape-generating moulding tools was from 40 to 60%. It was found that the increase in the thickness of the moulded package of the polymeric composite material resulted not only in a higher supplied power for the heating system, but also in a complication of the method for system control, because of the growing exothermic effect of the binder curing reaction. For composite products based on Hysol EA 9396 binder, thicknesses more than 4 mm are critical, because it is not possible to cope with the self-heating effect only by cooling with ambient air already utilized at the twentieth minute of the moulding process. The influence of the physical and mechanical characteristics of the moulding tool material and stiffening ribs was analysed in terms of energy consumption and controllability of the heating system. Fiberglass shows the lowest energy consumption. Heating of the aluminium and steel moulding tools for the same purpose will require 20% and 45% more power, respectively. An increase in the number of stiffening ribs has a strong effect on the heat removal of the heating system. With a small number of aluminium ribs it is not possible to maintain the specified temperature–time regime for a fiberglass moulded package of 5 mm thick with the use of the equipment. However, when the number of stiffeners is increased to 10, the exothermic effect of the reaction becomes smoother and then the heating equipment can cope with the task. An experimental prototype of heating equipment of moulding tools for the manufacturing of structures of polymeric composite materials, as well as a flexible thermal blanket for repair of non-separable structures, were developed. The results can be the basis for a new method of optimal design of parameters of moulding tool structure at minimal heat removal to the environment.

The shipbuilding industry, engine manufacturing, aviation, rocket and space technology are promising fields of application for polymeric composite materials. Shape-generating moulding tools with internal heating are used for the creation of a more economically viable method of moulding of internally heated composite structures. The use of a fine-fibered resistive structure in the heated tools allows implementation of effective heating of the composite and elimination of the need for expensive and energy-intensive heating equipment. The aim of this paper was the reduction of energy consumption for internally heated moulding tools by choosing the optimal parameters for their resistive layer. A method for determination of the parameters of the moulding tool resistive layer was developed. This method allows calculation of the heating layer parameters and implementation of the specified time–temperature regime for moulding of the composite structure. It was shown that energy saving for the heated fiberglass shape-generating moulding tools was from 40 to 60%. It was found that the increase in the thickness of the moulded package of the polymeric composite material resulted not only in a higher supplied power for the heating system, but also in a complication of the method for system control, because of the growing exothermic effect of the binder curing reaction. For composite products based on Hysol EA 9396 binder, thicknesses more than 4 mm are critical, because it is not possible to cope with the self-heating effect only by cooling with ambient air already utilized at the twentieth minute of the moulding process. The influence of the physical and mechanical characteristics of the moulding tool material and stiffening ribs was analysed in terms of energy consumption and controllability of the heating system. Fiberglass shows the lowest energy consumption. Heating of the aluminium and steel moulding tools for the same purpose will require 20% and 45% more power, respectively. An increase in the number of stiffening ribs has a strong effect on the heat removal of the heating system. With a small number of aluminium ribs it is not possible to maintain the specified temperature–time regime for a fiberglass moulded package of 5 mm thick with the use of the equipment. However, when the number of stiffeners is increased to 10, the exothermic effect of the reaction becomes smoother and then the heating equipment can cope with the task. An experimental prototype of heating equipment of moulding tools for the manufacturing of structures of polymeric composite materials, as well as a flexible thermal blanket for repair of non-separable structures, were developed. The results can be the basis for a new method of optimal design of parameters of moulding tool structure at minimal heat removal to the environment.
Self-Heating Mould for Composite Manufacturing
Keywords: resistive element; internal heating; exothermic effect; heating system power; laying pitch; thermal blanket; resistive element; internal heating; exothermic effect; heating system power; laying pitch; thermal blanket